A new cuticle scale hydrolysing protease from beauveria brongniartii - Erlacher, Angelika (2006)
From a screening for the production of new proteases specific for cuticle scales, Beauveria brongniartii was selected producing an alkaline Ca++ dependent protease. The purified had a molecular weight of 27 kDa and a pI value of 8.0. Substrate specificities of model substrates (wool with partially removed cuticles treated with SDS) were analyzed by protein release, dissolved organic carbon (DOC) and nitrogen analysis. The C/N ratio of released material turned out to be a good parameter to determine the site of action of proteases on fibres. Compared to other enzymes, the fungal protease preferentially hydrolyzed cuticle scales and has thus a potential for antishrinking pre-treatment of wool fabrics.